2014
DOI: 10.1175/mwr-d-13-00175.1
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Variability and Multiscale Interactions during Spring in West Africa

Abstract: The West African monsoon (WAM) is a vital source of rainfall for the African Sahel. In addition to the agricultural benefit of its rains, it benefits public health because bacterial meningitis outbreaks end with the monsoon onset. Outbreaks occur between December and May, a period of low humidity. Knowledge of the onset of high humidity could aid in predicting where the outbreaks will cease. Therefore, this study investigates the variability of atmospheric moisture during the spring over West Africa, character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 64 publications
2
21
0
Order By: Relevance
“…Their surface air parcel trajectory analysis, both horizontally and verti cally, revealed that the northeastern Atlantic, the Gulf of Guinea, the South Atlantic, North Africa, and the Mediterranean Sea are moisture sources for WA during the February-June period. Mera et al (2014) also found the levels of the atmosphere from which the air origi nated as the seasons progressed. Using the ECMWF global dataset at 600 hPa, Spinks and Lin (2015) Fig.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Their surface air parcel trajectory analysis, both horizontally and verti cally, revealed that the northeastern Atlantic, the Gulf of Guinea, the South Atlantic, North Africa, and the Mediterranean Sea are moisture sources for WA during the February-June period. Mera et al (2014) also found the levels of the atmosphere from which the air origi nated as the seasons progressed. Using the ECMWF global dataset at 600 hPa, Spinks and Lin (2015) Fig.…”
Section: Introductionmentioning
confidence: 93%
“…The study also found that the cold tongue regulates the timing and intensity of the coastal rainfall in the spring, while the SHL brings moisture into the continent. Mera et al (2014) studied the variability and transport of surface moisture in WA using NCEP global model analyses, satellite, and sta tions observations during the spring. Their surface air parcel trajectory analysis, both horizontally and verti cally, revealed that the northeastern Atlantic, the Gulf of Guinea, the South Atlantic, North Africa, and the Mediterranean Sea are moisture sources for WA during the February-June period.…”
Section: Introductionmentioning
confidence: 99%
“…The cold tongue regulates the timing and intensity of coastal rainfall in the spring, whereas the heat low brings moisture into the continent. Mera et al (2014) studied the variability and transport of surface moisture in WA using NCEP global model analyses, satellite, and station observations during the spring, which revealed that the Northeast Atlantic, the Gulf of Guinea, the South Atlantic, North Africa, and the Mediterranean Sea are moisture sources for WA during the February-June period.…”
mentioning
confidence: 99%
“…Processes that are known to influence the position of the ITD include interactions with the extratropics Vizy and Cook 2009;Knippertz and Todd 2010;Roehrig et al 2011; Denotes Open Access content. Roberts and Knippertz 2014), changes to the strength of the SHL (Parker et al 2005), African easterly waves (AEWs) on the African easterly jet (AEJ) (Berry and Thorncroft 2005;Couvreux et al 2010;Bain et al 2011), convectively generated cold pools (Flamant et al 2007;Cuesta et al 2010;Marsham et al 2008Marsham et al , 2013bGarcia-Carreras et al 2013;Roberts and Knippertz 2014), and eastward-propagating convectively coupled Kelvin waves (Mounier et al 2007;Mekonnen et al 2008;Mera et al 2014). Increased boundary layer moisture south of the ITD, in regions where the monsoon flow is deep, allows for the production of mesoscale convective systems (MCSs).…”
Section: Introductionmentioning
confidence: 99%
“…This makes the ITD especially important in the Sahel, whose inhabitants are heavily dependent on rain-fed agriculture. Additionally, the collapse of seasonal outbreaks of meningitis that affect the Sahel have been shown to be strongly linked to increases in humidity associated with northward surges of the monsoon flow (Mera et al 2014;Pandya et al 2015). These impacts on West African meteorology mean that there is great value in understanding the behavior of the ITD in models, observations, and such widely used products as operational analysis and reanalysis datasets.…”
Section: Introductionmentioning
confidence: 99%